Subadditivity and contestability in the postal sector: Theory and evidence - Toufic M. El Masri (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
Several studies have been conducted to analyze whether a regulation of the postal sector as a monopoly is actually efficient by examining its cost structure. The authors detected significant scale economies only in the delivery function and hence demonstrated a necessity for competition in the upstream operations. The primary purpose of this paper is to summarize the basic conditions of natural monopoly theory and to review the approaches and results of the studies dealing with this topic. Despite the importance of contestability in this context, previous literature concentrates only on the subadditivity aspect. The existence of economies of scale does not inevitably justify a governmental maintenance of the monopoly if the market is contestable. In this respect, further research is needed in order to account for contestability.
Keywords: D24; L51; L97; L22; 330; Postal Sector; Scale Economies; Subadditivity; Contestability; Postdienst; Natürliches Monopol; Potenzieller Wettbewerb; Skalenertrag; Betriebliche Wertschöpfung; Theorie